2012
DOI: 10.1111/j.1365-2184.2012.00814.x
|View full text |Cite
|
Sign up to set email alerts
|

Caspase‐mediated programmed cell death pathways as potential therapeutic targets in cancer

Abstract: The caspase family is well characterized as playing a crucial role in modulation of programmed cell death (PCD), which is a genetically regulated, evolutionarily conserved process with numerous links to many human diseases, most notably cancer. In this review, we focus on summarizing the intricate relationships between some members of the caspase family and their key apoptotic mediators, involving tumour necrosis factor receptors, the Bcl-2 family, cytochrome c, Apaf-1 and IAPs in cancer initiation and progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(97 citation statements)
references
References 59 publications
(55 reference statements)
4
86
0
1
Order By: Relevance
“…This initiates the apoptosis cascade, finally resulting in apoptosis. The activation of the caspase family is an important prerequisite for apoptosis since the caspase family activates apoptosis-related proteases when apoptosis occurs (32,33). We analyzed changes in the activation of caspases-9, -8 and -3 following treatment with embelin and found a significant increase in the activation of caspase-9, -8 and -3 with the occurrence of brain glioma apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…This initiates the apoptosis cascade, finally resulting in apoptosis. The activation of the caspase family is an important prerequisite for apoptosis since the caspase family activates apoptosis-related proteases when apoptosis occurs (32,33). We analyzed changes in the activation of caspases-9, -8 and -3 following treatment with embelin and found a significant increase in the activation of caspase-9, -8 and -3 with the occurrence of brain glioma apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, in this contact, the S1 caspase pocket, which is responsible for caspase substrate selectivity, remains free. Studies have shown that the linker region between the BIR1 and BIR2 domain in the XIAP protein has no function in caspase 3 and 7 inhibition as it was previously thought (7,13,17,18).…”
Section: Mechanism Of Caspases Inhibitionmentioning
confidence: 99%
“…If the heterodimer of caspase 9 is formed, there is no possibility of forming a supportive sequential element (L2 loop) which is a characteristic of homodimerisation and is thereby inactive. It is interesting that cIAP1 and cIAP2 cannot inhibit caspase 9 by preventing homodimerisation as XIAP can, because they do not contain the special sequence of four amino acids (12,13,18).…”
Section: Mechanism Of Caspases Inhibitionmentioning
confidence: 99%
“…2A, treatment of cells with cordycepin or TRAIL alone induced a slight loss of MMP in Hep3B cells; however, combined treatment with cordycepin and TRAIL caused a significant concentration-dependent induction of MMP loss. In particular, the anti-apoptotic Bcl-2 family molecules such as Bcl-2 and Bcl-xL, and IAP family members protect some tumor cell lines from TRAIL-induced apoptosis (22)(23)(24); therefore, we investigated the expression levels of members belonging to the Bcl-2 and IAP family. As shown in Fig.…”
Section: Effects Of Cordycepin and Trail Co-treatment On The Expressimentioning
confidence: 99%